Revisiting emerging market multinational enterprise views: The Goldilocks story restated - Arikan, Ilgaz; Arikan, Asli M.; Shenkar, Oded (Journal of International Business Studies, 2022)
We revisit the new perspectives that explain the internationalization and growth of multinational enterprises (MNEs) in emerging markets (EMs). Do we need a new theory for EM MNEs? Are the new theorizing efforts seeking the “just right” approach as in the Goldilocks story justified? We beg to disagree. We draw attention to the foundations of current international business (IB) and organization theories, rooted in culture, history, institutions, economics, strategy, and market dynamics to meet the challenges of theorizing the new EM MNE views. We offer complementary explanations on how to develop a more comprehensive approach, elaborate on the underlying assumptions and theoretical underpinnings of extant theories, elucidate their boundary conditions, and suggest how to alleviate the lack of systematic contextualization and directionality in causal relationships. We assert that while some EM MNEs display competitive advantages vis-à-vis their counterparts, not all possess superior capabilities compared to their advanced market rivals; as we exemplify, cases should not be generalized to the population but rather to theory.